Evaluation of Sustainable Environmentally Friendly Agriculture: Empirical Evidence in Ngawi Regency - Rita Parmawati; Amin Setyo Leksono; Aminudin Afandhi; Soemarno Soemarno; Akhmad Adi Sulianto (The University of Lampung, 2026)
Ngawi Regency is a major rice production center in East Java, playing a strategic role in supporting food security. However, conventional farming practices that depend heavily on chemical inputs have caused environmental degradation, soil nutrient imbalance, and reduced farmer welfare. To address these issues, the local government implemented the Sustainable Environmentally Friendly Agriculture (PRLB) program to promote a more adaptive and sustainable system. This study evaluates the sustainability status of PRLB across five dimensions—ecological, economic, social, technological, and institutional—and identifies key leverage factors. A multidimensional quantitative approach using Multi-dimensional Scaling (MDS) with RAP-FARM software was applied. Data were collected from 204 farmers and experts, supported by institutional records. The analysis included the calculation of sustainability indices, identification of sensitive attributes through leverage analysis, and Monte Carlo validation. Results show that PRLB is moderately sustainable, with an overall index of 67.28 on a 0–100 scale. Dimension scores were 63.43 (ecology), 69.04 (economy), 71.30 (social), 65.30 (technology), and 67.32 (institutional). Sensitive attributes include organic fertilizer use, waste management, by-product valorization, farmer group participation, youth regeneration, and extension services. Monte Carlo validation confirmed stable results. Overall, PRLB shows positive progress but requires strengthening, particularly in ecological, technological, and institutional aspects.